Design of miner type identification mechanism based on reputation management model - Jiaren YU; Youliang TIAN; Hui LIN (网络与信息安全学报)
In the public mining pool, miners can freely enter the mining pool to submit proof of work to obtain rewards, and there are no conditions to restrict different types of miners.There will be malicious miners submitting invalid workloads and miners not submitting workloads in the mining pool, occupying the verification computing resources of the mining pool, reducing the verification efficiency of the mining pool, and causing the mining pool system to collapse.Aiming at the problem that it is difficult to distinguish the type of miners in the mining pool, which leads to the collapse of the mining pool system, a reputation management mechanism was introduced to measure the behavior of miners, and contracts were deployed to prevent miners from colluding with the pool manager.A design of miner type identification mechanism based on reputation management model was proposed.A reputation mechanism was constructed to measure the behavior of miners.When a miner conducts malicious behavior, the miner's reputation value would be lowered.When the miner's reputation value was less than the reputation threshold of the mining pool, the system would remove the miner, so that the miner can no longer enter the mining pool to submit proof of work and get rewards.The miners in the mining pool were dynamically updated by Markov process, so that the miners in the mining pool were conducting honest behaviors and submitting proof of work.At the same time, a reward system was designed to motivate the miners in the mining pool, and smart contracts were deployed in the mining pool to prevent miners from collusion with the mining pool manager.Finally, analyzing the scheme from the perspective of security and performance, the proposed scheme was not only safe in the process of miners submitting proof of workload, but also solved the problem of identifying miner types in public mining pools, thereby solving the problem of malicious miners submitting invalid workloads, eliminating malicious miners, and avoiding mining pools verifying invalid workloads, to improve the verification efficiency of the mining pool.